Vasoactive intestinal peptide impairs leucocyte migration but fails to modify experimental murine colitis - Newman, R (Blackwell Science Inc, 2005)
Inflammatory bowel diseases are chronic inflammatory disorders of the gastrointestinal tract. Vasoactive intestinal peptide (VIP) is a neuropeptide with known anti-inflammatory activity. We have demonstrated previously that administration of VIP inhibits leucocyte migration in a murine model of delayed-type hypersensitivity, and anti-inflammatory efficacy is supported by other studies. The aim of this study was to investigate the VIP effects in a murine model of intestinal inflammation. Colitis was induced in BALB/c mice by a 2·5 mg enema of 2,4,6-trinitrobenzenesulphonic acid (TNBS) and the mice were killed on day 7. Mice were administered either a 3-day (therapeutic) or 7-day (prophylactic) constant infusion of VIP by subcutaneously implanted mini-osmotic pumps, or intraperitoneal (i.p.) injection of VIP on alternate days over 7 days. Clinical disease scores, weight changes, histopathology of colon tissues, plasma VIP levels, cytokine levels and chemotaxis of peripheral blood mononuclear cells were evaluated. After administration of TNBS, mice quickly developed severe colitis accompanied by dramatic body weight loss (20% by day 6) and high mortality (30%). Prophylactic treatment using high-dose VIP abrogated leucocyte chemotaxis; however, it failed to ameliorate the weight loss and mortality. Moreover, VIP delivered either by constant infusion or i.p. failed to modify the clinical, histological or cytokine markers of disease. Our studies show that, despite an ability to inhibit chemokine-induced chemotaxis of mononuclear cells, VIP was unable to modulate TNBS-induced colitis. This contrasts with the efficacy of VIP in models of mild inflammatory disease and suggests that VIP is unlikely to provide a useful model for novel anti-IBD therapy.